"I'm Being Forced to Make Decisions I Have Never Had to Make Before": Oncologists' Experiences of Caring for Seriously Ill Persons With Poor Prognoses and the Dilemmas Created by COVID-19. Issue 1 (January 2022) - Perumalswami, Chithra R.; Chen, Emily; Martin, Carly; Goold, Susan D.; De Vries, Raymond; Griggs, Jennifer J.; Jagsi, Reshma
Abstract : PURPOSE: The COVID-19 pandemic has created a new set of problems for clinicians. This study examines the experiences of oncologists providing care to seriously ill persons near the end of life in the context of the COVID-19 pandemic. METHODS: Between January 2020 and August 2020, we conducted semistructured, in-depth individual interviews with 22 purposefully sampled oncologists from practices enrolled in the Michigan Oncology Quality Consortium. Deidentified transcripts of the interviews were examined using thematic analysis. RESULTS: Our respondents described several novel problems created by the COVID-19 pandemic, including: (1) ethical challenges, (2) the need to manage uncertainty—physically and emotionally—on the part of both patients and oncologists, and (3) the difficulty of integrating technology and communication for seriously ill persons. These problems were made more complex by features of the pandemic: resource scarcity (and the need to fairly allocate poor resources), delays in care, high levels of fear, and the increased importance of advance care planning. Nonabandonment served as a way to cope with increased stress, and the use of telemedicine became an increasingly important medium of communication. CONCLUSION: This study offers an in-depth exploration of the problems faced by oncologists as a result of the COVID-19 pandemic and how they navigated them. Optimal decision making for seriously ill persons with cancer during the COVID-19 pandemic must include open acknowledgment of the ethical challenges involved, the emotions experienced by both patients and their oncologists, and the urgent need to integrate technology with compassionate communication in determining patient preferences.